Donor-Cell Origin High-Risk Myelodysplastic Syndrome Synchronous with an Intracranial Meningioma-Like Tumor, 8 Years after Allogeneic Hematopoietic Stem Cell Transplantation for Chronic Lymphocytic Leukemia. (3rd August 2017) - Brás, G.; Pinho-Vaz, C.; Campos, A.
Abstract : Secondary neoplasias are well known consequences of radiotherapy or chemotherapy for a primary cancer. In this report, we describe two rare secondary neoplasias occurring in the same patient: a meningioma-like intracranial tumor and high-risk myelodysplastic syndrome (MDS) of donor-cells origin, both diagnosed simultaneously, 8 years after an allogeneic hematopoietic stem cell transplantation (allo-HSCT) for chronic lymphocytic leukemia (CLL). Due to an engraftment failure during the first allo-HSCT of a matched related donor for CLL treatment, the salvage treatment was a second allo-HSCT. At the moment of meningioma-like tumor diagnosis, the patient was pancytopenic due to high-risk MDS, so it was decided to postpone a surgical intervention until hematological improvement. For the high-risk MDS of donor-cells origin the chosen treatment was induction with intensive chemotherapy. Due to refractory disease, the patient was treated with 5-azacitidine and donor-lymphocytes infusion with no response and, finally, a third allo-HSCT of a matched unrelated donor was performed. The patient died 6 months after the third allo-HSCT, in cytogenetic remission but without hematological recovery, due to an intracranial hemorrhage with origin in the meningioma-like tumor.